Formação do professor de Matemática: o lugar do cálculo diferencial e integral nas pesquisas acadêmicas - Machado, Jonatas Teixeira (2022)
University of Goiás (PPGECM/UFG). The research question is about: what do academic productions (dissertations and theses) reveal to us about the conception(s) of training Mathematics teachers in research on the teaching of CDI? Therefore, the main objective is to understand the conceptions of teacher training in Mathematics and in the integral differential calculus (CDI) resulting from academic productions that deal with these themes. We base our work on a critical and dialectical discussion about the phenomenon studied. The data collection procedure was based on the assumptions of Vosgerau and Romanowski (2014) and Saviani (2007) on theoretical research, of the State of Knowledge type. The research corpus was built from the productions (dissertations and theses) published in the CAPES Theses and Dissertations Bank, on the website of the Brazilian Digital Library of Theses and Dissertations (BDTD) and in the digital repository of each Graduate Program, from the following descriptors: “CDI”, “Teacher training”, “Education”, “Teaching”, “Graduate” and “Mathematics”. The data collection matrix built for the present research contained the following axes: conceptions of teacher training, CDI purposes for Mathematics teacher training and the CDI and its applications. After selection and full reading of the productions, the corpus of this research is composed of 11 theses and 22 dissertations, published between the years 2006 and 2019. As a result and its analysis, we identified that the main themes discussed in the research were: 1. dichotomy between teaching and learning; 2. use of ICT; 3. teaching and learning unit and 4. theoretical study. To a large extent, the conception of teacher education is mainly centered on constructivism (89%), whose foundation is given in formal logic and in which there is CDI reductionism, as well as mathematical formalism. There is a preponderance of the dichotomy between teaching and learning in the CDI, as well as a discussion of the use of educational technologies. A gap was also observed in the publications regarding discussions on the conceptual domain of the CDI. The recurrence of formalist logic in the training of Mathematics teachers is latent and directed to the discussion of specific and isolated situations, in procedures focused on topics of content or practice. The discussion of human work as an ontological factor appears in only one of the works that made up the research corpus. After analyzing the academic productions, we reflect that Mathematics teacher training should oppose the practice of immediate and formalist training, and should allow the process of teacher training on a critical and emancipatory basis, thus in the direct relationship of conceptual appropriation of mathematical knowledge. To this end, from the assumptions of the formation of the intellectual-critical professional, a way is proposed to overcome the constructivist and formalist character, which may constitute initial subsidies for the constitution of an epistemology of praxis.